Les problématiques de conception en formation à distance : Logiques et contextes du web - Jean-François Bourdet (Centre National d'Enseignement à Distance, 2014)
This paper focuses on relations between uses of the Internet (web 1.0, 2 and 3) and logics of design for the on line devices for education. It enlightens the change from a logic based on "surfing" to one strongly connected with a constructive approach, then to a questioning about the meaning of the curriculum itself.